Dynamics of Halal Supply Chain Development in Indonesia - Rozikin, Opik; Sonjaya, Adang; Susilawati, Cucu; bin Hussin, Hanafi (International Journal of Islamic Business and Economics (IJIBEC), 2024)
The article's main aim is to analyze the readiness of infrastructure to support the development of halal industrial areas in Indonesia. The discussion focused on aspects of infrastructure quality, halal awareness, and cooperation between organizations in the field of infrastructure. This study is proposed as literature research by examining various publications published in multiple media. The data that has been collected is validated and then analyzed using a descriptive-qualitative approach. Several halal industrial areas established in Indonesia are used as cases to discuss this study. This research shows that with Indonesia's sizeable Muslim population and solid demographic, religious, social and cultural capital, Indonesia has an excellent opportunity to become the centre of the world's halal industry. This support also takes the form of a high level of awareness regarding halal. However, Indonesia is still faced with various challenges, starting from suboptimal infrastructure and low awareness of halal certification, which results in limited availability of human resources and regulatory constraints so the halal industry can develop. The region's supply chain infrastructure and halal ecosystem accelerator could have been more optimal. This study can provide initial information on the development of halal industrial areas in Indonesia, but it requires further, more comprehensive research.